KONTROL ORANGTUA DAN DAMPAKNYA TERHADAP TINGKAT PERILAKU MEMBOLOS DI SMP - Irsyadi, Muhammad Iqbal; Ardi, Zadrian; Dwi Febriani, Rahmi; Meivilona Yendi, Frischa (Penerbit Lafadz Jaya, 2025)
This research is motivated by the phenomenon of truancy that still occurs among junior high school students. Parental control is believed to be an important factor that can influence truancy behavior. The objectives of this study were to determine the level of truancy behavior of students, the level of parental control, and the relationship between parental control and truancy behavior. This study used a quantitative approach with a descriptive correlational method. The sample consisted of 203 students of SMP Negeri 4 Lubuk Alung who were selected using a stratified random sampling technique. The instruments used were a parental control questionnaire and a truancy behavior questionnaire. The results of the analysis showed that parental control was in the high category, truancy behavior was in the low category, and there was a significant negative relationship with a coefficient of -,595 between parental control and truancy behavior. These findings emphasize the importance of parental involvement in supervising and guiding children in school life.